Diabetic retinopathy and the effect of pregnancy - P.S, Mallika; Tan , A.K; Aziz, S.; Asok, T.; Syed Alwi, S.A.R; Intan, G. (Academy of Family Physicians of Malaysia, 2010)
Pregnancy is associated with increased risk of development and progression of diabetic retinopathy (DR). Although pregnancy does not have any long term effect on DR, progression of retinopathy changes occur in 50%-70% of cases. The greatest risk of worsening occurs during the second trimester and persists as long as 12 months postpartum. The other factors found to be associated with its progression include duration of the diabetes, severity of retinopathy at conception, hyperglycaemic control, anaemia and progression of coexisting hypertension. Because of the increased risk of progression of the disease in pregnancy, conception should be delayed till the ocular disease is treated and stabilized and laser photocoagulation should be promptly instituted in all cases of severe non-proliferative retinopathy and should not be delayed till the patient develops early proliferative changes. Good diabetic control before and during pregnancy can help prevent this increase in the progression and serious vision loss.